Aural rehabilitation programme for hearing impaired: a psychosocial intervention - Juneja, Manisha K.; Sharma, Mamta; Singhal, Surinder (International Journal Of Community Medicine And Public Health, 2020)
Background: Hearing impairment i.e., reduced hearing acuity, has adverse effects on the physical, cognitive, emotional, behavioral, and social functions of an individual, resulting in passivity, social withdrawal, and negative impact on the quality of life (QOL). The present study aimed to determine whether participation in a counseling-based aural rehabilitation program and hearing aids would enhance the QOL of severely hearing-impaired by reducing their learned helplessness and social isolation. Methods: The study included 52 participants (35 males and 17 females) in the age range of 45-65 years having severe hearing loss with high perceived social isolation and learned helplessness and low quality of life. Scales used are Friendship scale for social isolation, LH scale for learned helplessness, and WHOQOL-Bref for quality of life. A paired t-test was applied to see the significant difference between pre and post scores. Results: Pre- and post-intervention analysis showed that learned helplessness and perceived social isolation was significantly reduced as a function of intervention with a substantially better quality of life. Conclusions: Aural rehabilitation program combined with hearing aids resulted in a better quality of life by reducing isolation and helplessness.